Controle de vibração em reatores elétricos através de absorvedores dinâmicos viscoelásticos - VALE, Alan Rafael Menezes do (Universidade Federal do Pará, 2011)
Equipments used in electric substations have specific functions in the functioning and maintenance of the functionality of such installations, being equipment applied to control reactive currents, short circuit currents and maneuver poles in transmission systems of electric energy. It was detected that some reactors in functioning had presented high levels of structural vibration. Two of these reactors operate in the substation of Rurópolis city, situated the west of Pará state. Another decurrent problem of the raised level of vibration of these structures is the generation of hot spots in the electromagnetic nucleus of the reactor, being able to generate bubbles of highly inflammable gases. The existence of these operational problems can cause to the North of Brazil Transmission System functional interruptions in the transmission of electric energy. That would cause in the North region and other linked ones (Northeast, Southeastern and Center-West) raised social and financial damages. The application of tools for reducing the vibrate-acoustic trouble (reduction of the levels vibration and, therefore, noise) can prevent structural and operational damages that result in its operative non-availability reducing, consequently, losses and the necessity of the development of equipment of cost raised with low indices of vibration. In the intention of if reducing such levels, it is considered the application of dynamic absorbers in the external structure of the reactors. With the calculated absorbers in amount, position and parameters (mass, stiffness and damping) expects to create a system syntonized with the frequency of the excitement of electromagnetic nature, that will absorb part of the vibratory energy of the reactor, having minimized raised detected levels and, therefore, all the subsequent problems. Viscoelastic materials will be used in the dynamic absorbers (with temperature and frequency dependent dynamic properties), because these materials to increase the field of activity of the dynamic absorbers, adjusting themselves it the raised verified modal density in the metallic shells of the reactor.